Foreign and Domestic Online Media Representation of Indonesian Minister of Finance: A Feminist Stylistics Approach - Tri Widarwati, Nunun; Purnomo, Budi; Unun Pratiwi, Veronika; Wicaksono, Bayu Hendro; Kiswaga, Godlove Elioth (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: Examination of gender representation and the portrayal of a prominent female public figure in both foreign and domestic online media. By applying a feminist stylistics approach, the study sheds light on the importance of fair and unbiased representation of female leaders in the media landscape, which can contribute to dismantling gender stereotypes and promoting gender equality in society. Methodology: This study employs a qualitative method to explore the portrayal of gender relations using Sara Mills' feminist stylistics framework, focusing on word, phrase/sentence, and discourse levels. Findings: The findings reveal that the representation of the Indonesian Minister of Finance in both foreign and domestic news sites exhibit specific yet distinct results, influenced by cultural norms and Sri Mulyani's reputation within Indonesia and internationally. Utilizing the three levels of analysis within the feminist stylistics theory framework, the study uncovers that the minister is addressed fairly and without explicit gender bias. Conclusion: This study highlights the importance of fair and unbiased representation of public figures in media by examining the portrayal of Indonesia's Minister of Finance through a feminist stylistics approach. Originality: This comprehensive analysis contributes to a deeper understanding of gender representation in media and highlights the importance of addressing public figures in a fair and unbiased manner.